Urban stream renovation: Incorporating societal objectives to achieve ecological improvements - Smith, Robert (2016)
Pervasive human impacts on urban streams make restoration to predisturbance conditions unlikely. The effectiveness of ecologically focused restoration approaches typically is limited in urban settings because of the use of a reference-condition approach, mismatches between the temporal and spatial scales of impacts and restoration activities, and lack of an integrative approach that incorporates ecological and societal objectives. Developers of new frameworks are recognizing the opportunities for and benefits from incorporating societal outcomes into urban stream restoration projects. Social, economic, cultural, or other benefits to local communities are often opportunistic or arise indirectly from actions intended to achieve ecological outcomes. We propose urban stream renovation as a flexible stream improvement framework in which short-term ecological and societal outcomes are leveraged to achieve long-term ecological objectives. The framework is designed to provide additional opportunities for beneficial outcomes that are often unattainable from ecologically focused restoration approaches. Urban stream renovation uses an iterative process whereby short-term ecological and societal outcomes generate public support for future actions, which may provide opportunities to address catchment-level causes of impairment that often exist across broad temporal scales. Adaptive management, education, and outreach are needed to maintain long-term public engagement. Thus, future work should focus on understanDing how ecological and societal contexts interact, how to assess societal outcomes to maintain stewardship, developing new methods for effective education and outreach, and multidisciplinary collaborations. We discuss potential abuses and the importance of linking societal outcomes to long-term ecological objectives. © 2016 by The Society for Freshwater Science.